If it's not what You are looking for type in the equation solver your own equation and let us solve it.
p in (-oo:+oo)
(1/3)*p = (5/3)*p // - (5/3)*p
(1/3)*p-((5/3)*p) = 0
(1/3)*p+(-5/3)*p = 0
-4/3*p = 0 // : -4/3
p = 0
p = 0
| -8x+7*(-56)=-56 | | 2x+-4=2 | | 3(3n+2)+2n=27+8n | | x+3x-13=7(x-9) | | 4x+15-9x=19-17x+12x-4 | | 18/840 | | 13x=5x | | 9000=x^2-18x+56 | | 4x^2+2x+3+[-2x]+6= | | -56=-8x+7 | | 2x+17-9x=20-18x+11x-3 | | -9+9*3= | | (2x-3y)+(x+3y)=180 | | 6x-4=6+4x | | 12x^3+16x^2-28x=0 | | (3/8)/(2/3)=24 | | 5w(12w+1)+12w+1= | | (2x^2+3x-54)/(x^2-5x+6)=0 | | (2x^2+3x-54)/(x^2-5x+6) | | 8000=x^2-18x+56 | | g(3)=9+5 | | 9n-19=5+n | | a+3=-11 | | 4x-5(1-2x)=6(x+3) | | 5(4x+2)=250 | | -3*3-9*-3= | | (3/8)/(2/3) | | -4=-4(-m-2) | | (64a^3*b^-6)^2/3 | | (64a^3b^-6)^2/3 | | x^3-2x-1=0 | | 2(-x+3)+5x= |